Culture of Intestinal Epithelial Cell Monolayers and Their Use in Multiplex Macromolecular Permeability Assays for In Vitro Analysis of Tight Junction Size Selectivity. (11th November 2020) - Pongkorpsakol, Pawin; Turner, Jerrold R.; Zuo, Li
Abstract: Tight junctions form a selectively permeable barrier that limits paracellular flux across epithelial‐lined surfaces. Small molecules (less than ∼8 Å diameter) can traverse the junction via the size‐ and charge‐selective, high‐conductance pore pathway. In contrast, the low‐conductance leak pathway accommodates larger macromolecules (up to ∼100 Å diameter) and is not charge‐selective. Flux across the tight junction–independent, high‐conductance, non‐selective, unrestricted pathway occurs at sites of epithelial damage. Cytokines can regulate each of these pathways, but commonly used measures of barrier function cannot discriminate between tight junction regulation and epithelial damage. This article describes methods for culturing intestinal epithelial cell monolayers and assessing the impact of cytokine treatment on leak and unrestricted pathway permeabilities. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Generation and culture of cell monolayers in Transwells Basic Protocol 2 : Assessment of cytokine (IFNγ and TNF) treatment effects on barrier function Support Protocol : Immunofluorescent staining of monolayers Basic Protocol 3 : Multiplex flux assay